U.S. Monetary Policy Normalization and Global Interest Rates - Caceres, Carlos (IMF Working Papers; Working Paper ;, 2016)
As the Federal Reserve continues to normalize its monetary policy, this paper studies the impact of U.S. interest rates on rates in other countries. We find a modest but nontrivial pass-through from U.S. to domestic short-term interest rates on average. We show that, to a large extent, this comovement reflects synchronized business cycles. However, there is important heterogeneity across countries, and we find evidence of limited monetary autonomy in some cases. The co-movement of longer term interest rates is larger and more pervasive. We distinguish between U.S. interest rate movements that surprise markets versus those that are anticipated, and find that most countries receive greater spillovers from the former. We also distinguish between movements in the U.S. term premium and the expected path of risk-free rates, concluding that countries respond differently to these shocks. Finally, we explore the determinants of monetary autonomy and find strong evidence for the role of exchange rate flexibility, capital account openness, but also for other factors, such as dollarization of financial system liabilities, and the credibility of fiscal and monetary policy.